Anticipating Risk for Human Subjects Participating in Clinical Research: Application of Failure Mode and Effects Analysis - Cody, Robert J. (Cancer investigation, 2006)
Failure Mode and Effects Analysis (FMEA) is a method applied in various industries to anticipate and mitigate risk. This methodology can be more systematically applied to the protection of human subjects in research. The purpose of FMEA is simple: prevent problems before they occur. By applying FMEA process analysis to the elements of a specific research protocol, the failure severity, occurrence, and detection rates can be estimated for calculation of a "risk priority number" (RPN). Methods can then be identified to reduce the RPN to levels where the risk/benefit ratio favors human subject benefit, to a greater magnitude than existed in the pre-analysis risk profile. At the very least, the approach provides a checklist of issues that can be individualized for specific research protocols or human subject populations.